Witchcraft, whites and the 1994 South African elections: Notes on the symbolic constitution of power in an Eastern Transvaal lowveld village - Isak A, Isak A. (My University, 1995)
The relationship between colonialism and witchcraft, as depicted in the ethnographic literature of central and southern Africa, presents an intriguing puzzle. The human myseries resulting from colonialism- such as the loss of land, poverty, disease, and labour exploitationare widely documented. It is also well known that witchcraft beliefs inscribe the causes of misfortune in tense social relationships. While studies recognize that colonialism has generated increased suspicions of witchcraft, they do not show that colonists are identified as witches. …. This article investigates, in greater depth, the intricate connections between experiences of colonial subjugation and African witchcraft beliefs. In contrast to the impression conveyed by the above-mentioned studies, I aim to demonstrate that colonists do not necessarily fall outside the parameters of witchcraft. Narratives of witchcraft can present a salient critique of the colonial order. Yet, I suggest that, criticisms of colonialism are less apparent in the sociology of witchcraft accusations, than in the symbolism of witchcraft beliefs.
African Studies Seminar series. Paper presented 27 February 1995.
Keywords: Witchcraft. South Africa. Mpumalanga; Elections. Social aspects. South Africa. Mpumalanga; Control (Psychology)